Estudio de factibilidad de la empresa Konecta con el propósito de ofertar el servicio de call center al mercado de México en el año 2020 - Chávez Miranda, Antonella (2019)
An analysis of the feasibility study of a Peruvian company was carried out to carry out an export of Call Center service in the Mexican market, so that information from the Konecta company will be collected regarding the competitive advantages it will provide and if That Free Trade Agreement (FTA) manner allows the company to differentiate itself from other Call Center service companies. The project will determine which competitive advantages of the Peruvian company Call Center Konecta will offer to the Mexican market in 2020. It will be answered under the qualitative method, based on the variables of the subject presented of which a semi-structured interview was conducted, which will take the company Konecta as a population as shown to the General Coordinator Mello Puchoc, Eduardo. This will aim to answer if the company should apply the FTA framework, to apply competitive advantages that it could give, such as rapid accessibility of information, allow the contracting company to focus on its core business, the effectiveness of the work and the confidence that will be added to meet certain quality requirements, to remain in the FTA.